Willingness to pay for flood risk management: a case study of Jammu and Kashmir - JAN, KOWSER ALI; Balaji, Dr. R; Rathar , Asif Ali (Jordan Journal of Agricultural Sciences, 2024)
All parts of the world are vulnerable to natural disasters. Flood hazards are the most typical causes of damage. People act preventatively up to the point where the predicted advantages (avoiding losses) outweigh the expenses, and this is influenced by knowledge (most of which is embedded in pricing) and limits on their resources. In addition, people vary in how much danger they're willing to take. This study analyses risk perception and attitudes that determine the flood risk response of the people in Jammu and Kashmir. A stated preference survey is carried out, with the potential impact of information being taken into account. Results indicate that several wealth composition variables, including housing value and annual income, have favorable impacts on risk perception. Whereas other factors, such as land value and durable goods value, negatively influence people's perceptions of risk. Additionally, other variables such as 'floods are exogenous to human control' show a very poor correlation with the willingness to pay for flood risk in the area. By their very nature, those who often engage in risky behavior include a need to cope with the occasional positive results.